Habitat Aedes Pradewasa dan Indeks Entomologi di 11 Kabupaten/Kota Provinsi Sumatera Selatan - Lasbudi Pertama Ambarita; Hotnida Sitorus; Rahayu Hasti Komaria (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Dengue fever and dengue haemorrhagic fever still becomes public health problems in South Sumatera Province with all of its regencies/cities have infested with Aedes aegypti. This research aimed to determine Aedes entomological indices and its breeding habitats. The research located at 11 regencies/cities, where in every regencies/cities determined two clusters (village) based on incidence rate in the last three years. Survey of preadult mosquito was carried out inside and outside areas of 1181 houses using single larva method with modification. The survey found that the dengue vector indices for house index, breteau index, and container index were at range 22,6% - 60,6%, 26,4 – 154,1 and 8,0% - 36,2% respectively. The most dominant water holding containers found infested with pre-adults mosquito were cement tanks (33,4%), followed by buckets (18,2%) and drums (14,7%). Inside houses, larva or pupae found dominants in cement tanks (44,3%), buckets (19,5%) and drums (13,9%), while outside of the house were used containers (20,7%), followed by drums (16,7%), buckets (15,0%) and used tires (11,9%). Statistical analysis by chi-square test showed a significant relationship between infested of Aedes pre-adults with characteristic of containers (colours, volume, location found and containers). Larval survey by visiting houses should carry out routinely and integrated into dengue vector control program.